Perception, Expansion and Organization of the Experience in the Construction of Phenomenologies (2020)
This article shows the research development on the role of perception in the expansion and organization of experience, as well as the pedagogical implications of the phenomenological stance and experimental practices in the classroom for the construction of explanations, specifically on the phenomenology of the hearing. The research shows reflections regarding the epistemological, when a knowledge construction route is chosen starting from phenomenology as an option for the classroom in the natural sciences class, likewise, of pedagogical aspects and what-to-do in the class of sciences from an experimental stance not corroborative, but enriching the experience of the subject, which is expressed through speaking, speaking and acting, and of course the disciplinary field as a space for discussion and construction of explanation of a common phenomenon, but That rarely is subject to reflection such as hearing, this knowledge problem is not inscribed from any specific discipline but is spoken from an undifferentiated context of the natural sciences, where the source, the medium and the receiver are related as elements that make up the phenomenon of study.